2005
DOI: 10.1172/jci25764
|View full text |Cite
|
Sign up to set email alerts
|

Brain glucagon-like peptide-1 increases insulin secretion and muscle insulin resistance to favor hepatic glycogen storage

Abstract: Intestinal glucagon-like peptide-1 (GLP-1) is a hormone released into the hepatoportal circulation that stimulates pancreatic insulin secretion. GLP-1 also acts as a neuropeptide to control food intake and cardiovascular functions, but its neural role in glucose homeostasis is unknown. We show that brain GLP-1 controlled wholebody glucose fate during hyperglycemic conditions. In mice undergoing a hyperglycemic hyperinsulinemic clamp, icv administration of the specific GLP-1 receptor antagonist exendin 9-39 (Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
243
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(269 citation statements)
references
References 70 publications
18
243
0
8
Order By: Relevance
“…Studies in two MODY genotypes, HNF-1α/β (also known as HNF1A/B), have reported differential effects of HNF-1β and HNF-1α on hepatic insulin sensitivity, with normal plasma glucagon levels and unaffected peripheral insulin sensitivity, and it has been proposed that the site of defect is located in the regulation of insulin action by HNF-1β and its effect on gluconeogenesis [36]. Intra-cerebral administration of a GLP-1 receptor agonist caused a fourfold increase in insulin secretion and enhanced liver glycogen storage in mice [37]. It remains to be determined whether TCF7L2 exerts a direct or indirect (via the central nervous system) influence on hepatic gluconeogenesis, glycogenolysis and/or glycogen synthesis, explaining its effect on EGP in the basal state as well as during insulin infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in two MODY genotypes, HNF-1α/β (also known as HNF1A/B), have reported differential effects of HNF-1β and HNF-1α on hepatic insulin sensitivity, with normal plasma glucagon levels and unaffected peripheral insulin sensitivity, and it has been proposed that the site of defect is located in the regulation of insulin action by HNF-1β and its effect on gluconeogenesis [36]. Intra-cerebral administration of a GLP-1 receptor agonist caused a fourfold increase in insulin secretion and enhanced liver glycogen storage in mice [37]. It remains to be determined whether TCF7L2 exerts a direct or indirect (via the central nervous system) influence on hepatic gluconeogenesis, glycogenolysis and/or glycogen synthesis, explaining its effect on EGP in the basal state as well as during insulin infusion.…”
Section: Discussionmentioning
confidence: 99%
“…The pumps were filled either with NaCl (0.9%) or LPS (from Escherichia coli 055:B5; Sigma, St. Louis, MO) to infuse 300 g ⅐ kg Ϫ1 ⅐ day Ϫ1 for 4 weeks. For the clamp studies, an intrafemoral catheter was indwelled as previously described (18). Insulin sensitivity was assessed by the euglycemic-hyperinsulinemic clamp as described (19).…”
Section: Methodsmentioning
confidence: 99%
“…An oral glucose tolerance test was performed 7 weeks after the beginning of the feeding period [7,28,29]. Six-hour-fasted mice received an oral load of glucose (Fluka, Buchs, Switzerland) of 3 g/kg body wt with a 660 g/l glucose solution.…”
Section: Oral Glucose Tolerance Testmentioning
confidence: 99%